Membentuk Peserta Didik Mengakui dan Menghargai Keberagaman Agama - Yemima Meidina Rista Br Sembiring; Edelweis Pardosi; Hisardo Sitorus (Lembaga Pengembangan Kinerja Dosen, 2026)
This paper discusses the role of education in shaping students' ability to recognize and appreciate religious diversity within Indonesia's pluralistic society. Indonesia, as a pluralistic nation, boasts a diversity of ethnicities, cultures, and religions, which demands the instilling of tolerance from an early age, particularly through educational institutions. Students are understood as individuals developing intellectually, morally, socially, and spiritually, requiring systematic guidance to understand differences as a gift from God. Recognizing and appreciating religious diversity is not merely about passive tolerance but also encompasses the ability to respect others' beliefs, engage in dialogue, and coexist peacefully without losing one's faith identity. Through education, particularly Christian Religious Education and Pancasila Education, values ​​of tolerance can be instilled through curriculum integration, teacher role models, an inclusive school environment, and practices such as opportunities to worship according to one's religion, interfaith cooperation, and social activities. Teachers play a strategic role as facilitators and role models in fostering empathy and appreciation for differences. Various strategies such as integrating multicultural values, providing worship spaces, strengthening cooperation, and cultivating mutual respect have proven effective in developing tolerant character in students. Research results indicate that education that emphasizes the value of tolerance aligns with the spirit of Pancasila and the teachings of Christ's love in the Bible. Therefore, developing students who value religious diversity is a long-term investment in creating a peaceful, just, and civilized society. Education that prioritizes inclusivity provides a crucial foundation for a generation capable of becoming agents of peace amidst the nation's diversity.